2016
DOI: 10.1310/hpj5102-149
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Stewardship Knowledge, Attitudes, and Practices among Health Care Professionals at Small Community Hospitals

Abstract: Background Very little is known about antimicrobial stewardship knowledge, attitudes, and practices (KAP) among health care practitioners in small, community hospitals (SCHs) compared to large community hospitals (LCHs). Objective To compare infectious diseases (ID) clinical resources and describe KAP pertaining to antimicrobial stewardship among prescribers, pharmacists, and administrators from a large hospital network including a comparison between SCHs and LCHs. Methods An anonymous 48-item antimicrobial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
5
9
2
Order By: Relevance
“…Approximately 80% of pharmacists were in favour and agreed that AMS programs improve patient care, which is aligned with the findings by Erku DA et al, where 86.3% of pharmacists were in favour of this. Research in other parts of the world also supports our findings that pharmacists and other health care professionals were in favour of an AMS program [46]. Similarly, AMS has been implemented in the majority of European countries in order to reduce the abuse and misuse of antimicrobials, the associated risk of resistance and adverse events [21] expenditure, the prevalence of resistant pathogens [47,48], and improve clinical outcomes [47,49].…”
Section: Discussionsupporting
confidence: 75%
“…Approximately 80% of pharmacists were in favour and agreed that AMS programs improve patient care, which is aligned with the findings by Erku DA et al, where 86.3% of pharmacists were in favour of this. Research in other parts of the world also supports our findings that pharmacists and other health care professionals were in favour of an AMS program [46]. Similarly, AMS has been implemented in the majority of European countries in order to reduce the abuse and misuse of antimicrobials, the associated risk of resistance and adverse events [21] expenditure, the prevalence of resistant pathogens [47,48], and improve clinical outcomes [47,49].…”
Section: Discussionsupporting
confidence: 75%
“…Almost 90% (74 of 84) of clinicians in our study hospitals who responded to the survey agreed that AS was important for patients; more than 55% (48 of 83) agreed that pharmacist antibiotic recommendations could improve the care of their patients. Buckel et al 14 polled pharmacists and prescribers at 20 community hospitals; both groups agreed that antimicrobials were overused in their hospitals. This increasing awareness of the importance of stewardship and acceptance of stewardship strategies in the community hospital setting is important.…”
Section: Discussionmentioning
confidence: 99%
“…Previous surveys of smaller hospitals have shown that only 50%-58% of hospitals have access to ID physicians [28,29]. In Utah, only 1 of 15 small hospitals within the Intermountain network had access to an inpatient ID consultation in 2014 [30].…”
Section: Infectious Diseases Physician and Pharmacy Leadershipmentioning
confidence: 99%